Reorientations mediated by translational displacements in confined liquid crystals studied by field cycling NMR relaxometry and Monte Carlo simulations - Grinberg, Farida (Diffusion Fundamentals, 2007)
Ordering effects and low-frequency molecular dynamics in the nematic liquid crystals confined in mesoscopic pores was studied with the help of field cycling (FC) Nuclear Magnetic Resonance (NMR) relaxometry and Monte Carlo simulations. Proton relaxation rates were measured above the bulk isotropisation temperature in the broad frequency range between 2 kHz and 7 MHz. The average pore radii of confinements were between 1.5 and 15 nanometers. The relaxation dispersion curves in the confined materials exhibited strong deviations from the behaviour in bulk. In a few kHz range, a dramatic enhancement of the relaxation rates exceeding two orders of magnitude compared to the bulk sample was observed. The low-frequency value of the relaxation rate exhibited a strong dependence on the pore size. Experimental findings were interpreted in terms of the surface induced orientational order and diffusion between the sites with different orientations of local directors. The analysis was supported by Monte Carlo simulations of the reorientations mediated by translational displacements (RMTD) in spherical cavities.